Strategi Pemberdayaan Masyarakat Melalui Inovasi Ekonomi Kreatif - Mega Sari (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The creative economy is considered to have a strategic role in national economic development, where the creative economic system is believed to be a problem solver in the global economy. Because apart from playing a role in economic growth and employment absorption and being able to survive amidst unfavorable economic conditions/monetary crisis. Apart from that, the contribution of the creative economy sector to the development of the Indonesian economy includes, among other things, increasing GDP. This research data consists of primary data and secondary data. The population in this research is all creative economy business actors in Kemiling District. The sample uses Purposive Sampling. As for the results of this research, community empowerment can be carried out through the awareness stages, the Understanding stage, the utilization stage and the Use of Results stage.